Designing an English Syllabus for Teachers of biMBA AIUEO - Siti Tuti Alawiyah (Universitas Bunda Mulia, 2018)
Nowadays, the numbers of pre-schools (Pendidikan Anak Usia Dini) which is established by Rukun Tetangga in society and also established by foundation or personal are getting increased. In a such condition, it makes parents think to deliver their kids to study in a pre-school that provides English Curriculum. Therefore, school foundation always tries hard in order to be the best school which has English lesson. At first, biMBA (bimbingan minat baca anak) only provides calistung program (baca tulis hitung). Due to the request from parents and the reality that many pre-schools have provided English subject, Mitra (who manage) biMBA decided to open English class in biMBA. Unfortunately, many teachers at biMBA AIUEO do not have English background. It can be assumed that they might produce mistakes and errors in pronunciation and spelling. That is why, English course is necessary to improve their English skills mainly at pronunciation and spelling. Before designing the course, needs analysis should be conducted in order to know what teachers need during the course later. The steps will be begun through distributing questionnaires to the teachers and an interview with their Mitra to obtain more insights about teacher’s knowledge. Afterwards, the results of the needs analysis will be interpreted to design a syllabus for them. It is believed that the syllabus based on learner’s needs will be more effective, and the learners’s goal to learn English can be achieved as well.Keywords: Teachers biMBA AIUEO, ESP, Needs Analysis, Present Situation Analysis (PSA), Learning Situation Analysis (LSA), Target Situation Analysis, Syllabus